Peran Pendidikan Akhlak Berbasis Al-Qur’an dalam Mengatasi Perilaku Bullying di SD Islam Terpadu Ummi A’yuni - Malika Shaqi Irawan; Farid Adnir (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Bullying behavior is still a serious problem in the educational environment because it has the potential to hinder the development of students from social, emotional, and academic aspects. This study aims to identify the forms of bullying that occur in the Ummi A'yuni Integrated Islamic Elementary School and examine the role of moral education based on Qur'an values in its prevention and handling. The research uses a qualitative approach with a descriptive design, involving four informants consisting of school principals, teachers, students, and parents through purposive sampling techniques. Data were collected through observation, interviews, and documentation studies, then analyzed using the interactive model Miles, Huberman, and Saldaña which included data reduction, data presentation, and conclusion drawn. The results showed that the most dominant form of bullying was verbal, in the form of ridicule, mockery, physical humiliation, and giving negative nicknames. In addition, physical bullying was also found in the form of light fights and hitting, although the frequency was lower. Qur'an-based moral education has proven to play an important role in overcoming bullying behavior through habituation of Islamic behavior, the use of polite language, teacher examples, giving advice, and cooperation between schools and parents. QS values. Al-Hujurat verses 11 and 13 are the foundation for instilling mutual respect and maintaining good relations. Thus, Qur'an-based moral education can be an effective strategy to prevent and reduce bullying in elementary schools.